2022
DOI: 10.3390/ph15030385
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols as Inhibitors of Antibiotic Resistant Bacteria—Mechanisms Underlying Rutin Interference with Bacterial Virulence

Abstract: The rising incidence of antibiotic resistant microorganisms urges novel antimicrobials development with polyphenols as appealing potential therapeutics. We aimed to reveal the most promising polyphenols among hesperetin, hesperidin, naringenin, naringin, taxifolin, rutin, isoquercitrin, morin, chlorogenic acid, ferulic acid, p-coumaric acid, and gallic acid based on antimicrobial capacity, antibiofilm potential, and lack of cytotoxicity towards HaCaT, and to further test its antivirulence mechanisms. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 76 publications
2
33
0
Order By: Relevance
“…As indicated in the literature, hesperetin can also inhibit bacterial biofilms. Previous study [ 19 ] has confirmed significant antibiofilm potential of hesperetin towards P. aeruginosa IBRS P001, with hesperetin being among the strongest antibiofilm polyphenols among the 11 compounds examined. Another study has established minimal biofilm inhibitory concentrations of hesperetin (MBIC 50 ) towards S. aureus RN4220 and S. aureus SA1199B at 4 µg/mL and 32 µg/mL, respectively [ 20 ].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…As indicated in the literature, hesperetin can also inhibit bacterial biofilms. Previous study [ 19 ] has confirmed significant antibiofilm potential of hesperetin towards P. aeruginosa IBRS P001, with hesperetin being among the strongest antibiofilm polyphenols among the 11 compounds examined. Another study has established minimal biofilm inhibitory concentrations of hesperetin (MBIC 50 ) towards S. aureus RN4220 and S. aureus SA1199B at 4 µg/mL and 32 µg/mL, respectively [ 20 ].…”
Section: Discussionmentioning
confidence: 64%
“…Previous study of hesperetin has indicated its low inhibitory potential towards S. aureus (MIC > 1 mg/mL) [ 17 ], as confirmed also in this study (MIC > 4 mg/mL). Moreover, stronger antibacterial potential for hesperetin was noticed in the study of Choi et al [ 18 ], who determined MIC at 0.125 mg/mL, and in the study of Ivanov et al [ 19 ], with MIC 0.5 mg/mL, both towards S. aureus . In this previous study [ 19 ] hesperetin exhibited identical antibacterial potential as its glycoside hesperidin, suggesting that sugar moiety does not have impact on antibacterial properties of this flavonoid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial capacity of extracts Cs7, Cs8, and Cs9 against Gram-negative bacteria, Salmonela Typhimurium, Escherichia coli , and Enterobacter cloacae , may be related to the presence of flavonoid compounds, namely quercetin, naringenin, and isorhamnetin, whose antibacterial potential has been described previously on several occasions [ 30 , 31 , 32 ]. In the current study, extract Cs1, the extract with the highest swertiamarin content, was the most effective in reducing the growth of Listeria monocytogenes , displaying an MIC of 0.5 and MBC of 1 mg/mL, while extract Cs2 was more effective in reducing the growth of Gram (+) bacteria than of Gram (−) bacteria.…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, the bactericidal effect of aqueous and ethanolic extracts could be attributed to the phenolic compounds, alkaloids, carbohydrates and ketoses identified in the studied organs of this plant. Indeed, the antimicrobial properties of these phytocompounds have been demonstrated in numerous studies carried out on various bacterial strains [20][21][22] .…”
Section: The Percents Reduction Of Dpph Radical By Eaq and Eethmentioning
confidence: 99%